NORMOLIPEMIC TUBEROUS XANTHOMAS - Singh, Ajay Pal (Medknow Publications, 2009)
Xanthomas are often a manifestation of underlying lipid abnormalities. A 50-year-old male presented to our hospital with the lesions of multiple tuberous xanthomas all over the body. Routine investigations and systemic examination were normal. Lipid profile was within normal range and serum protein electrophoresis showed normal pattern. Histopathology from a nodular lesion showed collection of foamy macrophages in the dermis. We present a case of normolipemic tuberous xanthomas, which is an uncommon occurrence.